Improving Interpersonal Communication Capability of Indonesian Workers In South Korea - Misnan Misnan; Kim Soo II; Agus Hitopa Sukma; Hiswanti Hiswanti; Iswahyu Pranawukir; Mayang Riyanti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The aim of this community activity is as an effort to improve the interpersonal communication skills of Indonesian workers (TKI) in South Korea. Good interpersonal communication skills are an important key in adapting to different cultural work environments and building effective relationships with colleagues, superiors and the surrounding community. The method used is online counseling. The targets are migrant workers who work in South Korea. The problem solving model used includes: identifying factors that influence the interpersonal communication skills of migrant workers in South Korea, such as differences in language, culture and communication norms. The results and discussion include a review of strategies and approaches that can be used to improve the interpersonal communication skills of migrant workers, including communication skills training, use of modern communication media and increased cultural understanding. Apart from that, this activity has provided important insights for the government, labor placement agents and TKI themselves in their efforts to improve work quality, adaptation and social interaction in their respective work environments.